Effect of Job Status, Gender, and Employees’ Achievement Motivation Behavior on Work Performance: a Case Study of Selected Local Government Employees in Ekiti State, Nigeria - Ogunleye, Adedeji J.; Osekita, Damilola A. (European Scientific Journal, ESJ, 2016)
This study investigated the effect of job status, gender, and employees’ achievement motivation behavior on work performance. Two hundred and seven (207) local government employees’ opinions were sampled using the achievement motivation questionnaire and the perceived work performance questionnaire. Seven hypotheses were developed and tested using 2 x 2 x 3 Analysis of Variance (ANOVA) statistics. Results confirmed that job status [F (2,206) =5.05, p05]. A significant interaction effect of gender and job status; gender and level of achievement motivation behavior; and job status and level of achievement motivation behavior were also found on work performance. However, there was no significant interaction effect that existed between gender, job status, and the level of achievement motivation behavior on work performance [F(2,206)=.217, p>.05]. Findings were discussed in the light of available literature and it is recommended that efforts should be made to discourage discriminative behavior among sexes while also closing gaps in level managers’ hierarchies and categorizations. This is particularly in terms of derivable incentives, benefits, and pay on their jobs to have a significant impact on the work performance of employees.